Chromatin remodeler ALC1 prevents replication-fork collapse by slowing fork progression. - Masato Ooka; Takuya Abe; Kosai Cho; Kaoru Koike; Shunichi Takeda; Kouji Hirota (PLoS ONE, 2018)
ALC1 (amplified in liver cancer 1), an SNF2 superfamily chromatin-remodeling factor also known as CHD1L (chromodomain helicase/ATPase DNA binding protein 1-like), is implicated in base-excision repair, where PARP (Poly(ADP-ribose) polymerase) mediated Poly(ADP-ribose) signaling facilitates the recruitment of this protein to damage sites. We here demonstrate the critical role played by ALC1 in the regulation of replication-fork progression in cleaved template strands. To analyze the role played by ALC1 as well as its functional relationship with PARP1, we generated ALC1-/-, PARP1-/-, and ALC1-/-/PARP1-/- cells from chicken DT40 cells. We then exposed these cells to camptothecin (CPT), a topoisomerase I poison that generates single-strand breaks and causes the collapse of replication forks. The ALC1-/- and PARP1-/- cells exhibited both higher sensitivity to CPT and an increased number of chromosome aberrations, compared with wild-type cells. Moreover, phenotypes were very similar across all three mutants, indicating that the role played by ALC1 in CPT tolerance is dependent upon the PARP pathway. Remarkably, inactivation of ALC1 resulted in a failure to slow replication-fork progression after CPT exposure, indicating that ALC1 regulates replication-fork progression at DNA-damage sites. We disrupted ATPase activity by inserting the E165Q mutation into the ALC1 gene, and found that the resulting ALC1-/E165Q cells displayed a CPT sensitivity indistinguishable from that of the null-mutant cells. This observation suggests that ALC1 contributes to cellular tolerance to CPT, possibly as a chromatin remodeler. This idea is supported by the fact that CPT exposure induced chromatin relaxation in the vicinity of newly synthesized DNA in wild-type but not in ALC1-/- cells. This implies a previously unappreciated role for ALC1 in DNA replication, in which ALC1 may regulate replication-fork slowing at CPT-induced DNA-damage sites.